Wpływ opadów atmosterycznych na gospodarkę wodną gleb autogenicznych przyległych do odkrywek kopalni węgla brunatnego = Effect of atmospheric precipitation on water regime of autogenic soils adjacent to lignite opencast mines - Owczarzak, Wojciech; Mocek, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the influence of atmospheric precipitation on the state of moisture content of autogenie soils situated in the neighbourhood of lignite opencast workings. The problem was analysed within the span of 35 years taking into account both the amount and distribution of precipitation throughout the year as well as during the vegetation season.
Keywords: 3 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zrównoważona gospodarka zasobami naturalnymi" (24-25.06.2004)